2019
DOI: 10.1007/s11769-019-1085-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Suitable Habitat for Lycophytes and Ferns in Northeast China: A Case Study on Athyrium brevifrons

Abstract: Suitable habitat is vital for the survival and restoration of a species. Understanding the suitable habitat range for lycophytes and ferns is prerequisite for effective species resource conservation and recovery efforts. In this study, we took Athyrium brevifrons as an example, predicted its suitable habitat using a Maxent model with 67 occurrence data and nine environmental variables in Northeast China. The area under the curve (AUC) value of independent test data, as well as the comparison with specimen coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In this study, the results showed that the AUC given FC = LQ, RM = 1.5 for the parameter ROC curve was 0.9388, which is higher than that of Atrium brevifrons (0.901) [58], Tags lucida (0.92) [54], Homoia riparia (0.899) [59], and Phenacoccus madeirensis (0.9177) [60], which indicates that the simulation effect of the MaxEnt model of the potential geographical distribution area of S. cathayensis is accurate and reliable. In order to reduce errors, 144 combinations of features in ENMeval data packets were called in R software.…”
Section: Bioclimatic Predictors and Model Performancementioning
confidence: 56%
“…In this study, the results showed that the AUC given FC = LQ, RM = 1.5 for the parameter ROC curve was 0.9388, which is higher than that of Atrium brevifrons (0.901) [58], Tags lucida (0.92) [54], Homoia riparia (0.899) [59], and Phenacoccus madeirensis (0.9177) [60], which indicates that the simulation effect of the MaxEnt model of the potential geographical distribution area of S. cathayensis is accurate and reliable. In order to reduce errors, 144 combinations of features in ENMeval data packets were called in R software.…”
Section: Bioclimatic Predictors and Model Performancementioning
confidence: 56%
“…Although it is impossible to simulate the potential distribution of species with few sites, the prediction of the distribution pattern of D. validus is helpful for the discovery and conservation of narrow-range species in their corresponding habitats. Multi-model intercomparison studies have reported that the MaxEnt model, which is based on the maximum entropy principle, typically outperforms other SDMs in terms of high tolerance and high predictive accuracy, particularly for small sample sizes [56][57][58]. In this study, less distribution point information was used to predict the MaxEnt model, and the results showed that the cross-validation AUC of the D. validus model was 0.751 and the TSS value was 0.526, further supporting the suitability of our ArcGIS-based MaxEnt model.…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution models (SDMs) are the most powerful and widely used tools for evaluating geographical distributions in space and time and predicting species habitat preferences [11]. Among SDMs, the Bioclimate Analysis and Prediction System (BIOCLIM), the Ecological Niche Factor Analysis (ENFA), the Genetic Algorithm for Rule-Set Production (GARP), and Maximum Entropy Modeling (MaxEnt) have been commonly used in recent years [12].…”
Section: Introductionmentioning
confidence: 99%